If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(3x-3=4x+1.x)
We move all terms to the left:
(3x-3-(4x+1.x))=0
We add all the numbers together, and all the variables
(3x-3-(+5x))=0
We calculate terms in parentheses: +(3x-3-(+5x)), so:We get rid of parentheses
3x-3-(+5x)
determiningTheFunctionDomain 3x-(+5x)-3
We get rid of parentheses
3x-5x-3
We add all the numbers together, and all the variables
-2x-3
Back to the equation:
+(-2x-3)
-2x-3=0
We move all terms containing x to the left, all other terms to the right
-2x=3
x=3/-2
x=-1+1/2
| 2x+32/5=5x-4/5 | | 2=-0.01x | | N+3n=188 | | H=8(4b)^2+2 | | 2x+1/4=-3/4x | | (5x+11=x-5,x) | | 10x+23=17x-37 | | X+19=-2x | | 9x=10x+7 | | 5x+11=x-5,x | | (X+4)x=165 | | 18-0.33x=-7 | | 20x-3=17x-36 | | 2/3+n=7/3 | | 6*14=n | | 5(3x+12)-9=6 | | 16w=6+40 | | 16w=16+40 | | 2.1n-531=18 | | x/3+x+20=180 | | y=183 | | -5(w+3)=-5w+1 | | -4/5(x-1/4)=3/7 | | 1/2(-4x+8)=-40 | | 6x+11=-2-8 | | 3y+(4y-40)=180 | | 1x+11=-2-8 | | 2x+11=-2-8 | | 8x+11=-2-8 | | x+88+40=5x | | 6÷7×7÷6x=140÷1×6÷7 | | 6(k–2)=36 |